Inkonstitusional Bersyarat dan Problem Kepastian Hukum dalam Pengujian Peraturan Perundang-Undangan - Atiek Pratiwi Putri Naue; Cassis Merinthia Ariapramuda; Wicipto Setiadi; Kaharuddin Kaharuddin (Lembaga Yasin AlSys, 2026)
The existence of Indonesia as a state based on law (rechtsstaat) places the Constitutional Court in a central position in guaranteeing constitutional supremacy and protecting citizens’ rights through a judicial review mechanism that is final and binding. However, the application of the conditionally unconstitutional decision model in the formal review of the Job Creation Law has given rise to debate regarding the stability of the national legal system because, on the one hand, it seeks to uphold democratic procedures, but on the other hand, it has the potential to create legal uncertainty with systemic impacts on society. This study aims to analyze the problems in the application of conditionally unconstitutional decisions in the formal review of laws and to formulate solution-oriented measures to strengthen legal certainty. This study employed a normative legal research method with statutory and conceptual approaches, which were analyzed descriptively-prescriptively based on various secondary legal materials. The results show that the practice of conditional unconstitutionality has transformed the role of the Constitutional Court from a negative legislator into a positive legislator that actively forms new norms. However, this practice has also created executorial obstacles and juridical ambiguity due to the absence of clear indicators and limitations in organic regulations. Thus, this study emphasizes the importance of redefining decision indicators that include deadlines for annulment, proportional room for institutional compromise, and original authority in reformulating execution in order to realize legal objectives that harmonize justice, expediency, and legal certainty for justice seekers in Indonesia.